2022
DOI: 10.3389/fpubh.2022.929407
|View full text |Cite
|
Sign up to set email alerts
|

Changes of factors associated with vaccine hesitancy in Chinese residents: A qualitative study

Abstract: IntroductionThere is an urgent need to address vaccine hesitancy to achieve booster vaccination. This study aimed to reveal the factors associated with vaccine hesitancy (including COVID-19 vaccine) among Chinese residents, address modifications of the factors since the previous year, and propose vaccination rate improvement measures.Materials and methodsThis qualitative return visit study was performed between January and mid-February 2022, following the last interview conducted between February and March 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Our study revealed that, as of January 2023, the estimated COVID-19 vaccination rate in LAM patients residing in China was approximately 77.34%. In China, the COVID-19 vaccine hesitancy rate is approximately 8% [ 19 ], with safety and efficacy being the most common reasons for hesitancy [ 20 ]. According to reports from July 23, 2022, the COVID-19 vaccination rate in mainland China was 89.7% [ 21 ], indicating that the vaccination rate among the Chinese LAM population is low.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that, as of January 2023, the estimated COVID-19 vaccination rate in LAM patients residing in China was approximately 77.34%. In China, the COVID-19 vaccine hesitancy rate is approximately 8% [ 19 ], with safety and efficacy being the most common reasons for hesitancy [ 20 ]. According to reports from July 23, 2022, the COVID-19 vaccination rate in mainland China was 89.7% [ 21 ], indicating that the vaccination rate among the Chinese LAM population is low.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study focused on vaccine confidence and acceptance among numerous other factors that could drive vaccine hesitancy and deter children and seniors' COVID-19 vaccine uptake. Studies suggest that differences in sociodemographic structures, health literacy, prevalence of chronic diseases, distributions of vaccine supplies, convenience to vaccinations, trust towards healthcare systems, governments, and vaccine developers impact vaccination coverages [35][36][37][38][39][40] . While vaccine confidence and acceptance are important attributes of vaccine uptake, our findings are not to be interpreted as the sole indicator of vaccination behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Improved understanding of the comparative risk-benefit profiles (especially regarding reactogenicity) is critical as additional COVID-19 vaccine options and doses become available and the world considers transitioning to annual vaccination. Lower levels of reactogenicity will likely help to optimize COVID-19 vaccine uptake and reduce vaccine hesitancy [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%